Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1046/j.1365-2672.1998.853568.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection and characterization of a novel antibacterial substance produced by a Lactobacillus delbrueckii strain 1043

Abstract: A novel antibacterial substance produced by a strain isolated from Bulgarian yellow cheese was characterized. The producer strain was identified by molecular typing to belong to the species Lactobacillus delbrueckii, which is a rare producer of bacteriocins. The inhibitory agent was heat stable and active against lactic acid bacteria species and several food‐borne pathogens : Listeria monocytogenes, Staphylococcus aureus, Enterococcus faecalis, Escherichia coli, Yersinia enterocolitica and Y. pseudotuberculosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 30 publications
(36 reference statements)
1
31
0
1
Order By: Relevance
“…Samples were incubated for 2 h at 30³C and the pH was adjusted to 6.8. For protease-susceptibility assays, culture supernatants were incubated for 2 h with hydrolases (proteinase K, trypsine, papaine, glucoamylase, lipase, K-amylase and lysozyme) at a ¢nal concentration of 1 mg ml 31 [12]. For testing residual inhibitory activities, each sample was assayed in the agar well di¡usion test (ADT) [13].…”
Section: E¡ects Of Temperature Ph and Proteases On Lactococcin Mmfiimentioning
confidence: 99%
“…Samples were incubated for 2 h at 30³C and the pH was adjusted to 6.8. For protease-susceptibility assays, culture supernatants were incubated for 2 h with hydrolases (proteinase K, trypsine, papaine, glucoamylase, lipase, K-amylase and lysozyme) at a ¢nal concentration of 1 mg ml 31 [12]. For testing residual inhibitory activities, each sample was assayed in the agar well di¡usion test (ADT) [13].…”
Section: E¡ects Of Temperature Ph and Proteases On Lactococcin Mmfiimentioning
confidence: 99%
“…Nisin has been shown to inhibit the growth of L. monocytogenes in several fermented dairy products (Davies, Bevis, & Delves-Broughton, 1997;Ferreira & Lund,, 1996), however, nisin-resistant strains (Gravesen, Jydegaard Axelsen, Mendes da Silva, Hansen, & Knochel, 2002;Mazzotta & Montville, 1997) have been identified suggesting a need for additional "food-grade" bacteriocins. Bacteriocins with antilisterial activity have been identified in dairy starter LAB, including Streptococcus thermophilus (Fontaine & Hols, 2008;Gilbreth & Somkuti, 2005;Marciset, Jeronimus-Stratingh, Mollet, & Poolman, 1997;Villani et al, 1995) and L. lactis (Akcelik, Tukel, Ozcengiz, & Akcelik, 2006;Elotmani, Revol-Junelles, Assobhei, & Millere, 2002;Ferchichi, Frere, Mabrouk, & Manai, 2001;Kim, Kim, Kim, & Kim, 2006;McAuliffe et al, 1998), and in non-starter LAB (NSLAB) including lactobacilli (Corr et al, 2007;Ennahar et al, 1996;Holck, Axelsson, Birkeland, Aukrust, & Blom, 1992;Miteva et al, 1998;Mueller, Carrasco, Tonarelli, & Simonetta, 2009;Tichaczek, Vogel, & Hammes, 1993) and enterococci (Franz, van Belkum, Holzapfel, Abriouel, & Galvez, 2007;Khan, Flint, & Yu, 2010;Renye, Somkuti, Paul, & Van Hekken, 2009). …”
Section: Introductionmentioning
confidence: 96%
“…EPSs produced by LAB have several medicinal values, possessing antitumor, [2] antimutagenic, [3] antiulcer, [4] and antibacterial activities. [5] In addition, LAB have been shown to be effective as immunostimulators [6] and blood cholesterol-lowering agents. [7] It has been found that the above-mentioned medicinal events arise from the whole microorganisms or cell wall components or extracellular polysaccharides.…”
Section: Introductionmentioning
confidence: 99%